2022
DOI: 10.3390/ijerph19159078
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life after Bariatric Surgery—A Systematic Review

Abstract: Background: Most studies analyzing the health-related quality of life (HRQOL) after bariatric treatment ceased at five years post-surgery or even earlier, and it is unclear whether the HRQOL benefit persists for a longer time. This paper reviews sparse evidence regarding HRQOL in patients who underwent bariatric surgery at least nine years prior. Materials and Methods: A of PubMed, Scopus and Google Scholar between 2007–2021 was carried out for the studies investigating HRQOL as an outcome measure in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0
16

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 62 publications
(119 reference statements)
4
22
0
16
Order By: Relevance
“…These patients should be offered psychological intervention, which is likely to further improve the results of bariatric treatment. 14 Similar results were shown in a 3-year follow-up study in 2022. 15 A UK study 16 confirmed the wish for more psychological support related to, for example, eating behaviour.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…These patients should be offered psychological intervention, which is likely to further improve the results of bariatric treatment. 14 Similar results were shown in a 3-year follow-up study in 2022. 15 A UK study 16 confirmed the wish for more psychological support related to, for example, eating behaviour.…”
Section: Introductionsupporting
confidence: 80%
“…However, it was shown that some participants did not achieve expected results either in terms of HRQoL or weight loss. These patients should be offered psychological intervention, which is likely to further improve the results of bariatric treatment 14 . Similar results were shown in a 3‐year follow‐up study in 2022 15 …”
Section: Introductionsupporting
confidence: 68%
“…One of the most important reasons for people to undergo BSis to increase the QoL by increasing selfesteem and reducing anxiety and depression. 31 Sierżantowicz et al 10 have reported that the healthrelated QoLbenefit persists for a longer time, at least a 9-year follow-up after BS. According to Vieira et al 31 , BS improved the quality of life in women of reproductive age, reduced comorbidities and improved their sexual experience in emotional and physical fields.Silva et al 32 state that patients undergoing BS show improved psychological conditions after weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…For example, although several short-term studies have reported that bariatric surgery significantly decreases symptoms of depression and anxiety in the initial post-operative year [8][9][10][11], longer-term studies including a recent systematic review [12] have demonstrated that these improvements begin to deteriorate 2 to 3 years post-surgery [5,9,10,13,14]. Similar questions exist for quality of life outcomes following surgery and whether improvements in healthrelated quality of life persist over time [15].…”
Section: Introductionmentioning
confidence: 99%